Increased fluid intake for the prevention of urinary tract infection in adults and children in all settings: a systematic review. Issue 1 (January 2020) - Fasugba, O.; Mitchell, B.G.; McInnes, E.; Koerner, J.; Cheng, A.C.; Cheng, H.; Middleton, S.
SUMMARY: Background: Non-antibiotic interventions for urinary tract infection (UTI) prevention have been investigated as a strategy to reduce antibiotic prescribing for UTI and subsequent antibiotic resistance. Increased hydration is widely advocated for preventing UTI; however, evidence for its effectiveness is unknown. Aim: To systematically review the published literature on the effectiveness of increased fluid intake as a preventive intervention for UTI in adults and children in any setting. Methods: Five electronic databases were searched from inception to February 2019 to identify published randomized controlled trials (RCTs) and quasi-experimental studies evaluating the effectiveness of high (≥1.5 L/24 h) versus normal/low (<1.5 L/24 h) fluid intake for UTI prevention. The outcome was UTI incidence. Risk of bias was assessed using the Cochrane Collaboration's tool. Due to the small number of studies identified, meta-analysis was not possible. Hence a narrative synthesis was undertaken. Findings: Of the 2822 potentially relevant papers, two were eligible for inclusion: an RCT (individual randomization) and a cluster-RCT. Both studies differed regarding participants, setting, sample size, UTI definition, and intervention. The RCT was assessed as having a low risk of bias whereas the cluster-RCT had a high risk of bias. Only the RCT, which included healthy premenopausal women visiting primary care clinics, demonstrated statistical significance for the effect of high fluid intake for UTI prevention. Conclusion: The lack of enough adequately powered and robust RCTs highlights the need for further research on the effectiveness of this intervention for UTI prevention.